Woman carrier of cancer: nursing’s diagnoses the light of Orem’s theory - Fialho, Ana Virgínia de Melo; Pagliuca, Lorita Marlena Freitag (Rev Rene, 2000)
In the operacionalization of the nursing process the self-care should be stimulated for an active participation of the person in the treatment. The formulation of nursing diagnoses bases the interventions to leave of the clinical judgement of the answers or problems of the individual’s health, systematizing and standardizing the care that implies in incentive to the self care for better adaptation to the situation of disease or maintenance of the health. The objectives of this study are to describe the nursing assistance; to identify the diagnoses based in the Orem theory’s self care. It is a descriptive study, inside of approach qualitative, type case study, applied a woman cancer carrier. The results reveal the description of the nursing assistance through the nursing process implementation in the all Orem’s phases, in which the knowledge deficit and ineffective front individual were identified as priority for the assistance. It is ended that the nursing assistance was important for the acceptance and the patient’s adaptation, lacking of knowledge and self-care, that overcame the critical phase of the diagnosis and treatment.